2016
DOI: 10.1080/21645515.2016.1143158
|View full text |Cite
|
Sign up to set email alerts
|

Rabies post-exposure prophylaxis for a child with severe allergic reaction to rabies vaccine

Abstract: Most adverse events (AEs) during the immunization of rabies vaccine were slight, there was little information about the allergic reaction induced by rabies vaccines and had to stop or change the immunization program. Here, we reported a case that a 4-year-old boy had category II exposure to rabies and showed severe allergic reaction after being immunized with lyophilized purified vero cell rabies vaccine (PVRV). After the anti-allergy therapy with hormone, allergy testing indicated medium allergy to egg and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 7 publications
1
9
1
Order By: Relevance
“…Other rare presentation of anaphylaxis include nausea, vomiting, diarrhea, cramping, pain, tachycardia, hypotension, chest pain, cardiac arrest, metallic taste in mouth, uterine contraction, scrotal edema, dizziness, seizures, sense of impending doom. 2,4 Since the symptoms show multisystem organ involvement sometimes diagnosis of anaphylaxis can be difficult with atypical presentation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Other rare presentation of anaphylaxis include nausea, vomiting, diarrhea, cramping, pain, tachycardia, hypotension, chest pain, cardiac arrest, metallic taste in mouth, uterine contraction, scrotal edema, dizziness, seizures, sense of impending doom. 2,4 Since the symptoms show multisystem organ involvement sometimes diagnosis of anaphylaxis can be difficult with atypical presentation.…”
Section: Discussionmentioning
confidence: 99%
“…In such cases patients must be treated with epinephrine, antihistamine, steroids and intravenous fluids. 2 The risk of patient acquiring rabies must be considered carefully before deciding to discontinue the vaccine. 5 In this case, it was challenging to identify the cause of the AEs and offer prompt medication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study. 19 a child suffered from AEs was allergic to eggs and milk while the first vaccine applied to him after dog bite was stabilized by gelatin and components from cattle, so it finally concluded that the vaccine containing heterologous protein was the culprit to him. Occurrence of Henoch Schönlein purpura (HSP) in an adult patient post rabies vaccination was also rare and serious.…”
Section: Discussionmentioning
confidence: 99%